Development of Stable Homozygous Wheat/Amblyopyrum muticum (Aegilops mutica) Introgression Lines and Their Cytogenetic and Molecular Characterization - King, Julie; Newell, Claire; Grewal, Surbhi; Hubbart-Edwards, Stella; Yang, Cai-yun; Scholefield, Duncan; Ashling, Stephen; Stride, Alex; King, Ian P. (Frontiers in Plant Science, 2019)
Wheat is one of the world’s most important sources of food. However, due to its evolution it has a low genetic base which will severely limit the ability of breeders to develop new superior higher yielding varieties that are adapted to the changing environment. In contrast to wheat, its wild relatives provide a vast reserve of genetic variation for most, if not all, agronomically important traits. Genetic variation has previously been transferred to wheat from one of its wild relatives, Ambylopyrum muticum (previous known as Aegilops mutica). However, before the genetic variation available in this species can be assessed and exploited in breeding and for research, the transmission of the chromosome segments introgressed into wheat carrying it must first be stabilised. In this paper we describe the generation of 69 stably inherited homozygous wheat/Am. muticum introgression lines using a doubled haploid procedure. The characterisation and stability of each of these lines was determined via genomic in situ hybridisation and SNP analysis. The strategy that we are employing for the distribution and exploitation of the genetic variation from Am. muticum and a range of other species is discussed.